Papel do IFN-y e do óxido nítrico na patogênese do dengue experimental em camundongos - Caio Tavares Fagundes (2007)
Dengue is currently the most important mosquito-borne disease that affects humans and constitutes a serious world health problem. Although knowledge about the disease pathogenesis is incipient, an important role is attributed to cytokines in host response to infection. Among them, we highlight IFN-, a cytokine with important functions in immunity to infectious agents. In this work, we evaluated the role played by IFN- and by one of its effectors molecules, nitric oxide, during de response to Dengue virus infection. For this purpose, we used an animal model based in mice infection with a clinical Dengue-2 isolate, adapted to the murine host. Mice were able to produce IFN- after infection with Dengue virus. Furthermore, mice deficient in IFN- production (IFN--/-) presented higher lethality after infection with dengue virus. This reduced survival rate was associated by a more severe disease manifestation when compared to wild type infected mice, as assessed by increase in thrombocytopenia, haemoconcentration and hypernociception, besides elevated systemic TNF- and IL-6 concentrations. In addition, there was loss in liver chemokine production by infected IFN--/-, and increased neuthophil influx to lungs, when compared to control wild type infected mice. This enhanced susceptibility to infection was characterized by loss in control of viral replication after infection, what we deduced to be associated with reduced ability of NO-production by IFN--/- mice. Hence, iNOS-mediated NO production seemed important during dengue infection, as showed by increased susceptibility of iNOS-/- mice. These animals, akin to IFN--/- mice, presented enhanced lethality after infection, in addition to elevated platelet counts and reduced haemoconcentration. iNOS-/- mice also showed exacerbated TNF- and IL-6 level in circulation, and reduced tissue chemokine content and neutrophil infux to the lung. Finally, even able to produce high levels of IFN- during infection, iNOS-/- mice seemed to be unable to control dengue virus replication, as assessed by high viral titers in spleen of these mice. Then, we conclude that IFN--induced NO production is an important pathway during response to dengue virus infection. In the absence of these two molecules, there is reduced ability of viral replication control by the host, resulting in a more severe disease manifestation. Strategies capable to enhance production of these two molecules may result in benefits during the control of primary infection by Dengue virus.